2022
DOI: 10.1097/mco.0000000000000825
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal coronavirus disease 2019 manifestations in childhood

Abstract: Purpose of reviewThe pandemic of coronavirus disease 2019 , caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has emerged and caused a massive global health crisis. The aim of this review is first, to provide the latest evidence on what is known about the pathophysiology and the transmission of SARS-CoV-2 and then to focus on the manifestations of the gastrointestinal (GI) tract in children with COVID-19. Lastly, we summarise the impact of COVID-19 on patients with preexisting GI diseases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 113 publications
0
4
0
Order By: Relevance
“…The ACE2 receptor and the TMPRSS2 are co-expressed not only in the lungs but also in the esophageal, gastric, and small and large intestinal mucosa, making the entire GI tract highly susceptible to SARS-CoV-2 infection. 13 , 14 , 20 , 26 28 Of note, it seems that the expression of these proteins varies across ages. With increasing age, ACE2 and TMPRSS2 expressions decrease in the GI tract while increasing in the lungs.…”
Section: Covid-19 and The Gastrointestinal Tractmentioning
confidence: 99%
See 2 more Smart Citations
“…The ACE2 receptor and the TMPRSS2 are co-expressed not only in the lungs but also in the esophageal, gastric, and small and large intestinal mucosa, making the entire GI tract highly susceptible to SARS-CoV-2 infection. 13 , 14 , 20 , 26 28 Of note, it seems that the expression of these proteins varies across ages. With increasing age, ACE2 and TMPRSS2 expressions decrease in the GI tract while increasing in the lungs.…”
Section: Covid-19 and The Gastrointestinal Tractmentioning
confidence: 99%
“…Afterward, they are released into the GI tract, causing direct damage to the enterocyte and viral shedding in the stool. 13 , 26 , 30 , 31 Fecal excretion of SARS-CoV-2 is common. 14 , 26 In an early study from China Hua et al detected SARS-CoV-2 RNA in feces in 32/35 (91%) infected children, with viral shedding persisting up to 70 days.…”
Section: Covid-19 and The Gastrointestinal Tractmentioning
confidence: 99%
See 1 more Smart Citation
“…Since the common coexistence of GI and respiratory disorders in COVID-19 infection[ 9 , 32 ] and the potential detection of SARS-CoV-2 RNA in both oral and rectal swabs[ 33 , 34 ], Zhou et al [ 35 ] suggested a possible involvement of the axis in COVID-19 pathogenesis (Figure 2 ). As a consequence, the COVID-19 infection might act as a trigger for cytokine storm leading to multiorgan dysfunction including the gut.…”
Section: The Gut-lung Axis In Covid-19 Infectionmentioning
confidence: 99%